2021
DOI: 10.3390/ijms221910704
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenin and Copper Crossing in Wound Healing

Abstract: Angiogenesis plays a key role in the wound healing process, involving the migration, growth, and differentiation of endothelial cells. Angiogenesis is controlled by a strict balance of different factors, and among these, the angiogenin protein plays a relevant role. Angiogenin is a secreted protein member of the ribonuclease superfamily that is taken up by cells and translocated to the nucleus when the process of blood vessel formation has to be promoted. However, the chemical signaling that activates the prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 109 publications
(144 reference statements)
1
39
0
8
Order By: Relevance
“…It is known that copper ions are required for collagen synthesis, stimulate VEGF production, and enhance angiogenesis [43]. Moreover, angiogenin-bound copper is a potent inducer of blood vessel development, and it binds to endothelial cell receptors and extracellular matrix components [44]. Since in our work, we also developed PCL-Cu-COOH (containing active COOH groups), which promotes strong binding of protein factors and facilitates the proliferative activity of cells [45,46].…”
Section: Discussionmentioning
confidence: 96%
“…It is known that copper ions are required for collagen synthesis, stimulate VEGF production, and enhance angiogenesis [43]. Moreover, angiogenin-bound copper is a potent inducer of blood vessel development, and it binds to endothelial cell receptors and extracellular matrix components [44]. Since in our work, we also developed PCL-Cu-COOH (containing active COOH groups), which promotes strong binding of protein factors and facilitates the proliferative activity of cells [45,46].…”
Section: Discussionmentioning
confidence: 96%
“…This observation is intimately linked to the central node around which this manuscript develops, i.e., to highlight whether a greater intake of ANG at the cytosolic level could alter the cellular response following perturbations of homeostasis. This issue was addressed by the use of recombinant ANG (rANG) to exploit the well-established concept that the protein is also able to act as a paracrine factor [ 25 , 26 ]. The collected results ( Figure 7 ) clearly suggest that the pre-treatment of HaCaT cells with rANG causes a more incisive cellular response to a putative perturbation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that ANG, as a circulating protein induced during inflammation, exhibits microbicidal activity against bacterial and fungal systemic pathogens, suggesting that it can also contribute to systemic responses to infection [ 24 ]. ANG is also a paracrine agent that can be taken up by endocytosis into the cytoplasm of target cells [ 25 , 26 ]. Nevertheless, beyond the autocrine or paracrine origin, stress-induced ANG cellular activity is critically regulated by the endogenous inhibitor, RNH1, both in the nucleus and cytosol.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, collagen deposition in wound tissues is associated with enhanced angiogenesis [ 74 ]. Angiogenesis plays a key role in the wound-healing process and is involved in the migration, growth and differentiation of ECs [ 75 ]. The ability of naturally occurring compounds has been reviewed [ 76 ].…”
Section: Discussionmentioning
confidence: 99%